Identification of Science Misconceptions Using Two-Tier Multiple Choice for Elementary School Grade IV Students - Sadevi, Rista Ayu; Sayekti, Ika Candra (Profesi Pendidikan Dasar, 2023)
This study aims to identify the level of science misconceptions about plant parts and their function in fourth-grade students of Batumarta Public Elementary School. This study uses descriptive research with the quantitative method. The research was conducted at Batumarta Public Elementary School. The sampling using a saturated sampling technique. The sample of this study consisted of 28 students. The data collection instrument used two-tier multiple-choice questions that had previously been tested for construct validation with biologists, other lecturers, or supervisors. The data analysis technique uses data grouping and data interpretation. This misconception will be identified using a diagnostic test with a research instrument in the form of two-tier multiple-choice questions. Based on the results of the study, it was found that students who experienced misconceptions in the material of plant parts and their functions in the category of knowing concepts as much as 16.42%, students in the category of pure misconceptions as much as 18.03%, student category of misconceptions guessing as much as 15.88%, and students in the category of not understanding as much as 49.63%. the conclusion was that the students of Batumarta Public Elementary School experienced misconceptions in the very low category, namely as much as 18.03%.